Rights of Employees and Workplace Discrimination Phenomenon in Nigeria: Lessons from United States of America - Daudu S. O.; Osadolor, Ivie (LexScriptio A Journal of the Department of Jurisprudence and Public Law, 2024)
The rights of an employee are guaranteed and free from any form of discrimination. Despite the protection afforded by the relevant laws on labour, employment and productivity, some forms of discriminations still exist at the work place. The focus of this article is on the discriminations that inhere in employment and the rights of vulnerable individuals in the Nigeria workplace. The major objectives of this article is to identify the specific factors contributing to employment discrimination against vulnerable employees in Nigeria, such as age, gender, disability, ethnicity, religion and socio-economic background with a view to assessing the effectiveness of current measures and mechanisms in addressing employment discrimination in order to protect the rights of vulnerable employees in Nigeria. To achieve the aforementioned objective of the article, the doctrinal approach will be adopted. The authors will rely on texts, journal articles, case law, statutes, treaties and other international instruments on labour and employment in Nigeria with a view to drawing lessons from the United States of America. This article finds that vulnerable employees experienced discrimination in employment due to their personal characteristics such as race, ethnicity, gender, disability, age or sexual orientation. The article recommends the establishment of a dedicated body to investigate and resolve complaints of discrimination in employment at workplace in Nigeria. The article concludes that workplace discrimination is unhealthy and can affect the productivity of workers in Nigeria.